The Influence of Early analytic Philosophy on Kelsen’s Pure Theory - Abdullah Omar Alkholy (Journal of Legal Sciences, 2024)
Hans Kelsen’s account of legal positivism is unique in various respects, first in its logicist approach to legal facts. Kelsen has been recognized as the first jurist to have attempted to reduce law to pure logic of norms, distinct from truth-value propositional logic. Moreover, he introduced the entity of legal meaning as an abstract object distinct from a proposition as a meaning-bearing entity in propositional logic. Second, Kelsen invented the doctrine of "basic norm" and presented it as a necessary condition for the existence of legal discourse. The doctrine serves two functions: it gives logical unity to a legal system and solves the problem of infinite regress by alienating psychological elements from the law. Thirdly, he started what might be considered the linguistic turn in legal philosophy. Indeed, linguistic analysis of legal concepts and statements has become prevalent among legal positivists after Kelsen. The Hartian project may be considered a revision of Kelsen’s thesis in light of the earlier accounts of legal positivism and ordinary language philosophy within the analytic philosophy tradition. The distinctive features of Kelsen’s positivism and his innovative approach to the logic of legal norms are very similar to the rigid methodologies taken by early analytic philosophers toward logical and mathematical facts. Thus, the hypothesis under investigation in this article is that early analytic philosophy was in Kelsen’s intellectual background while he worked on his pure theory of law. The hypothesis relies on several similarities between Kelsen’s theory of pure law and the approach of early analytical philosophy in terms of motivation, methodology, and aims. The research was divided into three parts: The first discussed the nature of universal relations in law and their importance as necessary conditions for the existence of the legal system and legal discourse. The second section introduces the reader to the early analytic philosophy, its most important intellectual figures, methodologies, and main themes. Lastly, the article concludes by discussing the main findings and critique of the research hypothesis.